Multistep optimization of HyPix model for flexible vertical scaling of soil hydraulic parameters. (October 2022) - Pollacco, J.A.P.; Fernández-Gálvez, J.; Rajanayaka, C.; Zammit, S.C.; Ackerer, P.; Belfort, B.; Lassabatere, L.; Angulo-Jaramillo, R.; Lilburne, L.; Carrick, S.; Peltzer, D.A.
Abstract: Efficient simulation of water-flow processes in the vadose zone is crucial to increase agricultural productivity within environmental limits. This requires deriving detailed soil hydraulic parameters of the soil profile that is highly challenging, particularly for heterogeneous soils. We therefore developed an alternative indirect methodology to calibrate the hydraulic parameters from soil water content time series measured at multiple depths by using the new physically based hydrological model HyPix. We propose a novel, efficient, multistep optimization algorithm for layered soils that derives an optimal set of hydraulic parameters for a desired number of soil layers. For each selected soil layer, HyPix derives five physical, bimodal, Kosugi hydraulic parameters that describe the soil water retention and hydraulic conductivity by using a novel algorithm that reduces the degree of sensitivity and freedom of the parameters. The optimization algorithm upscales the soil hydraulic parameters by gradually incorporating the soil heterogeneity. This method overcomes the problems associated with optimization of the hydraulic parameters of each layer individually, which leads to poor results because it does not represent the cohesive soil water dynamics across the unsaturated zone. We tested the method using soil water content measurements at different depths at five heterogeneous experimental sites in New Zealand. We show how the accuracy of the simulated water balance components increases with the number of soil layers. The multistep optimization upscales a detailed, layered profile of soil hydraulic parameters into a model with fewer layers. The methodology developed provides an estimate of the uncertainty of using a reduced number of soil layers. We also show that a pedological description can provide an indication of the minimum soil layers of vertical discretization required to accurately compute the soil water balance components. Highlights: A hydrological model that solves the Richardson–Richards' equation allowing vertical scaling of hydraulic properties. Vertical multistep optimization of bimodal Kosugi hydrological parameters for layered soils. Accuracy of simulated water balance components and soil water content with different number of soil layers. Soil description informs the vertical discretization required to compute water balance components. Graphical abstract: Image 1